I. I. MOGILEY: PRAGMATIC TRANSFORMATIONS IN THE UKRAINIAN TRANSLATIONS OF THE CONTEMPORARY ENGLISH PROSE - MOGILEY, I. I. (Linguistic Bulletin (Movoznavchyi Visnyk), 2022)
Summary. Introduction. Pragmatic aspects in translating any supposed texts mean much for the efficiency of interpreting and reproducing the translated messages both in oral and written translation which generally means applying pragmatic transformations to obtain the functional equivalence of literary texts. Methods of tackling the pragmatic equivalence introduced by Prof. O. Selivanova include textual and pragmatic analyses of the extracts given as well as instances of phraseological, figurative, conceptual and megatextual transformations as means of analyzing the transformed structures and adapting them in the Ukrainian literary contexts. With this effect, the article regards the selected fragments in the aspect of securing the pragmatic information including transformations in translating original phraseological units, in substituting pragmatic categories of concept and figures of speech, or forms of megatextual comments and footnotes. Pragmatic transformations appear as well possible and proficient including finding possible equivalents in phraseology and merging pharaseological units, substituting elements of pragmatic meaning and concept type. Purpose. Sense of observing and tackling the phenomenon of pragmatic equivalence in the translated texts and their original counterparts lies in achieving completely eligible literary translations so that they would be perceived as the source work. The article deals with a number of fragments and examples from the 19th– 20th century English and American literature regarded in the pragmatic translation aspect. Methods. The article applies the contrastive methods to establish the differences in form and contents of the two-language comparative analysis, as well as descriptive passages, to fuller explain and provide the illustrative items. Results. Though pragmatic background seems to be rather inconspicuous in terms of general stylistic effect of translating literary texts, its structural role is quite meaningful and brings new or altered senses into the narration. The paper proved pragmatic aspect to be one of the most important for understanding and estimating the imagery of numerous texts under consideration. Originality. The transformation processes are regarded in a new perspective, that of a new approach to the problems of equivalence and adequate translation in the literary context, being supported with modern views on lingual and cognitive phenomena in the evolving communicative activity throughout the global functional and translating practices. Conclusion. Functional and stylistic equivalence is obviously perceived to be achieved through numerous translation devices including pragmatic transformations associated with several types of changes, most of which lie within the inner and contextual meaning of the lexical units and various textual phenomena in imagery of the text.